The Role of External Audit in Limiting Creative Accounting Practices in Light of International Standards from The Point of View of Certified Accountancy Experts in Iraq as a Model - Abdulrahman, Doaa Mohammed (Journal of Economics and Administrative Sciences, 2022)
This research aims to solve a problem in the field of accounting and financial knowledge in the world today, that is, the problem of creative accounting. Especially after the global financial crisis and the collapse of many large companies in the world, people find that they use creative accounting methods to distinguish them from reality, showing the results of their activities and their financial status. This research discusses the concept of creative accounting, the most important methods used in financial statements and its relationship with external auditing, and procedures to limit accounting creativity. This study uses descriptive analysis methods after confirming its theoretical aspects in practice. Using the statistical program Wolfram Alpha, the results of the questionnaire were distributed to registered Iraqi accounting experts and several results were obtained